Cognitive performance’s critical role in the progression from educational attainment to moderate to vigorous physical activity: insights from a Mendelian randomization study - Qi, Fang; Jinmin, Zhang (Frontiers in Psychology, 2024)
Introduction In individuals with high educational levels, moderate to vigorous physical activity (MVPA) is often elevated, yet the causal direction and the role of cognitive performance in this association remain ambiguous. Herein, Mendel randomization (MR) was employed to measure the causal relationship between education, cognitive performance, and moderate to vigorous physical activity. The purpose of this study was to analyze the causal effects of educational attainment on moderate-to-vigorous physical activity (MVPA) levels and to explore potential mediating factors. Methods Two-sample univariate MR analysis was conducted to assess the overall effect of education on moderate to severe physical activity. Besides, a two-step MR analysis was carried out to evaluate the mediating effect of cognitive performance on the impact of education on moderate to severe physical activity. Individuals included were exclusively of European ancestry, with data gathered from extensive genome-wide association studies (GWAS) on education (n = 470,941), cognitive performance (n = 257,841), and moderate-to-vigorous physical activity (MVPA) (n = 377,234). Educational attainment was measured by college graduation status. Cognitive performance encompasses not only psycho-motor speed, memory, and abstract reasoning abilities but also knowledge and skills acquired in professional domains. MVPA is defined as any physical activity that produces a metabolic equivalent (MET) of ≥3.0. Results The positive two-sample MR analysis showed that education level had a significant protective effect on MVPA deficiency (β = −0.276, 95% CI = −0.354 to −0.199, p = 2.866 × 10−12). However, the reverse two-sample MR analysis showed that MVPA had no significant causal relationship with education level (p = 0.165). Subsequently, the two-step MR analysis indicated that the potential causal protective effect of education on the risk of MVPA deficiency was mostly mediated by cognitive performance (mediating effect β = −0.235, 95% CI = −0.434 to −0.036, and the intermediary ratio was 85.061%). Discussion Cognitive performance holds considerable significance in the relationship between education level and MVPA. Consequently, the intervention of cognitive performance may greatly improve the risk of physical inactivity caused by education, thereby promoting individual health.